Neuroinflammatory signals enhance the immunomodulatory and neuroprotective properties of multipotent adult progenitor cells - Ravanidis, Stylianos (Stem Cell Res Ther, 2015)
INTRODUCTION: Stem cell-based therapies are currently widely explored as a tool to treat neuroimmune diseases. Multipotent adult progenitor cells (MAPC) have been suggested to have strong immunomodulatory and neuroprotective properties in several experimental models. In this study, we investigate whether MAPC are of therapeutic interest for neuroinflammatory disorders such as multiple sclerosis by evaluating their capacities to modulate crucial pathological features and gain insights into the molecular pathways involved. METHODS: Rat MAPC were treated with combinations of pro-inflammatory cytokines that are closely associated with neuroinflammatory conditions, a process called licensing. mRNA expression of immunomodulatory molecules, chemokines and chemokine receptors was investigated. The migratory potential of licensed rat MAPC towards a broad spectrum of chemokines was tested in a Transwell assay. Furthermore, the effect of licensing on the ability of rat MAPC to attract and suppress the proliferation of encephalitogenic T cells was assessed. Finally, neuroprotective properties of rat MAPC were determined in the context of protection from oxidative stress of oligodendrocytes. Therefore, rat MAPC were incubated with conditioned medium of OLN93 cells subjected to sublethal doses of hydrogen peroxide and the gene expression of neurotrophic factors was assessed. RESULTS: After licensing, a wide variety of immunomodulatory molecules and chemokines, including inducible nitric oxide synthase and fractalkine, were upregulated by rat MAPC. The migratory properties of rat MAPC towards various chemokines were also altered. In addition, rat MAPC were found to inhibit antigen-specific T-cell proliferation and this suppressive effect was further enhanced after pro-inflammatory treatment. This phenomenon was partially mediated through inducible nitric oxide synthase or cyclooxygenase-2. Activated rat MAPC secreted factors that led to attraction of myelin-specific T cells. Finally, exposure of rat MAPC to an in vitro simulated neurodegenerative environment induced the upregulation of mRNA levels of vascular endothelial growth factor and ciliary neurotrophic factor. Factors secreted by rat MAPC in response to this environment partially protected OLN93 cells from hydrogen peroxide-induced cell death. CONCLUSIONS: Rat MAPC possess immune modulatory and neuroprotective properties which are enhanced in response to neuroinflammatory signals. These findings thereby warrant further research to evaluate MAPC transplantation as a therapeutic approach in diseases with an immunological and neurodegenerative component such as multiple sclerosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13287-015-0169-z) contains supplementary material, which is available to authorized users.